Pengaruh Aromaterapi Lavender Terhadap Kualitas Tidur Ibu Hamil Trimester II dan III di Polindes Desa Lambu - Hairunnisyah Hairunnisyah; Ratih Kumorojati (Universitas Harapan Bangsa Purwokerto, 2023)
Background: Pregnant women often feel disturbed sleep patterns during the second and third trimesters of pregnancy. This happens because of changes in physiology and psychology. Physiological changes such as abdominal enlargement, anatomical changes and hormonal changes. Meanwhile, psychological changes are caused by excessive anxiety and fear for no reason. Eventually it leads to depression so that the quality of sleep is disturbed. Disturbed sleep quality can be overcome by non-pharmacological methods, namely by using lavender aromatherapy. Objective: The purpose of this study was to determine the effect of lavender aromatherapy on the quality of sleep of pregnant women in the second and third trimesters at the Lambu Village Polindes. Method: Pre-experimental research design with a pre-test post-test one group design. The population of all pregnant women who carried out examinations in October-November at the Lambu Village polindes were 20 pregnant women in the second and third trimesters with a minimum HPL at the end of November. Sampling was carried out using purposive sampling with 15 respondents. This study used lavender aromatherapy using a diffuser at night for 7 days. Pittsbrug sleep quality index (PSQI) sleep quality instrument which consists of 7 components. Data were analyzed using the Wilcoxon signed rank test. Result: Based on the results of the wilcoxon test, it shows that the p-value = 0.035 where the p-value is <0.05, which means that Ha or the hypothesis in this study is accepted. that is, there is an effect of lavender aromatherapy on the sleep quality of pregnant women in the second and third trimesters at the Lambu Village Polindes. It was proven that 10 out of 15 respondents (66.7%) had a change in sleep quality. Conclusion: There is an effect of lavender aromatherapy on the quality of sleep of pregnant women in the second and third trimesters at the Lambu Village Polindes. Keywords: Lavender Aromatherapy, pregnant women in the second and third trimesters, Sleep Quality